Production of light-flavor hadrons in pp collisions at √s=7 and √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Pachmayer, Yvonne C.; Reygers, Klaus; Schicker, Rainer; Schmah, Alexander; et al. (The European physical journal. C, Particles and fields, 2021)
The production of $$\pi ^{\pm }$$, $$\mathrm{K}^{\pm }$$, $$\mathrm{K}^{0}_{S}$$, $$\mathrm{K}^{*}(892)^{0}$$, $$\mathrm{p}$$, $$\phi (1020)$$, $$\Lambda $$, $$\Xi ^{-}$$, $$\Omega ^{-}$$, and their antiparticles was measured in inelastic proton-proton (pp) collisions at a center-of-mass energy of $$\sqrt{s}$$= 13 TeV at midrapidity ($$|y|<0.5$$) as a function of transverse momentum ($$p_{\mathrm{T}}$$) using the ALICE detector at the CERN LHC. Furthermore, the single-particle $$p_{\mathrm{T}}$$distributions of $$\mathrm{K}^{0}_{S}$$, $$\Lambda $$, and $$\overline{\Lambda }$$in inelastic pp collisions at $$\sqrt{s} = 7$$ TeV are reported here for the first time. The $$p_{\mathrm{T}}$$distributions are studied at midrapidity within the transverse momentum range $$0\le p_{\mathrm{T}}\le 20$$GeV/c, depending on the particle species. The $$p_{\mathrm{T}}$$spectra, integrated yields, and particle yield ratios are discussed as a function of collision energy and compared with measurements at lower $$\sqrt{s}$$and with results from various general-purpose QCD-inspired Monte Carlo models. A hardening of the spectra at high $$p_{\mathrm{T}}$$with increasing collision energy is observed, which is similar for all particle species under study. The transverse mass and $$x_{\mathrm{T}}\equiv 2p_{\mathrm{T}}/\sqrt{s}$$scaling properties of hadron production are also studied. As the collision energy increases from $$\sqrt{s}$$= 7-13 TeV, the yields of non- and single-strange hadrons normalized to the pion yields remain approximately constant as a function of $$\sqrt{s}$$, while ratios for multi-strange hadrons indicate enhancements. The $$p_\mathrm{{T}}$$-differential cross sections of $$\pi ^{\pm }$$, $$\mathrm {K}^{\pm }$$and $$\mathrm {p}$$($$\overline{\mathrm{p}}$$) are compared with next-to-leading order perturbative QCD calculations, which are found to overestimate the cross sections for $$\pi ^{\pm }$$and $$\mathrm{p}$$($$\overline{\mathrm{p}}$$) at high $$p_\mathrm{{T}}$$.
Im Titel steht "s" steht unter dem Wurzelsymbol
Gesehen am 21.04.2021